Robustness Testing of Satellite Attitude and Orbit Control Systems: A Proposal Guided by Two Model Based Testing Methodologies - Corsetti, Andre; Ambrósio, Ana Maria; Mattiello-Francisco, Maria de Fátima (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
Attitude and Orbit Control System (AOCS) is one subsystem of the Service Module of a satellite which mostly endures faults in space operations. The criticality and complex nature of the subsystem demands an extensive effort in its integration and controller's software testing, mainly for validating the Fault Detection, Identification and Recovery (FDIR) requirements. This paper presents a proposal of characterization of the mechanisms of FDIR in order to apply model-based testing methodologies to address the AOCS robustness aspect. Two testing methodologies named CoFI and InRob using respectively Finite State Machine and Timed Input Output Automata formalisms to model critical services will be used, highlighting the robustness properties of the services. The testing methodologies support integration testing and acceptance phase of AOCS software. This paper aims in describing the selection of the two test methodologies and presenting the approach for modelling FDIR.